2014
DOI: 10.4103/1463-1741.127849
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of rosuvastatin on noise-induced oxidative stress in rat brain

Abstract: The problem of noise has recently gained more attention as it has become an integral part of our daily lives. However, its influence has yet to be fully elucidated. Other than being an unpleasant stimulus, noise may cause health disorders through annoyance and stress, including oxidative stress. Rosuvastatin, a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, may possess antioxidant properties. Based on rat models, our project investigates the effect of rosuvastatin on noise-induced oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also, oxidative DNA damage (detected by the comet assay) was observed in the rat heart and adrenal gland on noise exposure ≥100 dB(A) ( 86 , 139 ). Cardiovascular therapy using the cholesterol lowering substance rosuvastatin effectively prevented these adverse effects ( 70 ).…”
Section: Effects Of Noise On Vascular Function and Oxidative Strmentioning
confidence: 99%
“…Also, oxidative DNA damage (detected by the comet assay) was observed in the rat heart and adrenal gland on noise exposure ≥100 dB(A) ( 86 , 139 ). Cardiovascular therapy using the cholesterol lowering substance rosuvastatin effectively prevented these adverse effects ( 70 ).…”
Section: Effects Of Noise On Vascular Function and Oxidative Strmentioning
confidence: 99%
“…Ambient noise can impair productivity, auditory health, and perceptions of employees and result in negative physiological and psychological consequences (Güvercin and Aybek, 2003). As the noise levels increase and the exposure to noise is lengthened, it becomes possible to observe the negative effects on the cardiovascular, gastrointestinal, endocrine, and nervous systems (Akyıldız, 1980, Ersoy et al, 2014). In most businesses, noise levels can reach the upper noise limits that may impair the employees' health.…”
Section: Introductionmentioning
confidence: 99%
“…In prior experimental studies in rats, researchers found MDA level to be high and SOD activity to be low with chronic noise exposure (100 dB for 4 hr/day over 20 days; Koc et al, 2015). Another group of researchers exposed rats to noise levels of 100 dB 4 hr/per day for 20 days and investigated oxidant and antioxidant parameters in both blood and brain tissue (Ersoy et al, 2014). They reported that SOD activity in both serum and brain tissue was significantly lower and MDA level in brain tissue was significantly higher in the noiseexposed group compared to the other groups.…”
Section: Discussionmentioning
confidence: 99%